A Thermo-Tunable Metamaterial as an Actively Controlled Broadband Absorber. (January 2023) - Xing, Xiao-Chang; Cao, Yang; Tian, Xiao-Yong; Wu, Lingling
Abstract: Metamaterials have attracted increasing attention in recent years due to their powerful abilities in manipulating electromagnetic (EM) waves. However, most previously reported metamaterials are unable to actively control full-band EM waves. In this paper, we propose a thermo-tunable broadband metamaterial (T-TBM) using paraffin-based composites (PD-Cs) with different phase transition temperatures. Active control of the T-TBM reflection loss peaks from low to high frequency is realized by manipulating the solid–liquid state of the PD-Cs at different phase transition temperatures. The absorption peak bandwidth (where the reflection loss value is less than −30 dB) can be changed, while the broad bandwidth absorption (where the reflection loss value is less than −10 dB) is satisfied by adjusting the temperature of the T-TBM. It is shown that the stagnation of the phase transition temperature of the PD-Cs in the T-TBM provides a time window for actively controlling the EM wave absorption response under different thermal conditions. The device has a broad application prospect in the fields of EM absorption, intelligent metamaterials, multifunctional structural devices, and more.